2021
DOI: 10.1308/rcsann.2020.7152
|View full text |Cite
|
Sign up to set email alerts
|

Day-case approach to immediate breast reconstruction: pushing the boundaries of ambulatory breast surgery in the post-COVID-19 era

Abstract: Introduction Day-case surgery is safe and efficacious for most breast surgical procedures. Limited data exist on its use in immediate breast reconstruction. We present our experience of day-case management of mastectomy with immediate pre-pectoral implant-based reconstruction (IBR). Methods Data were collected on 47 patients who underwent day-case skin-sparing (SSM) or nipple-sparing (NSM) mastectomy with pre-pectoral IBR between October 2017 and September 2019. Clinicopathological data were collected, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Specht et al 25 found, despite a small sample size, no complications were observed in a 30-day postoperative follow-up period of same-day discharge patients. Shaker et al 33 reported findings on immediate implant-based reconstruction, which found comparable rates to national standards in terms of postoperative infection, implant loss, and readmission rates, with no significant difference in overall complications. A series of studies by Dumestre et al 34 in 2017 reported similar data on implant-based reconstruction with same-day discharge compared with overnight admission, and focused on postoperative complications within a 30-day period.…”
Section: Discussionmentioning
confidence: 99%
“…Specht et al 25 found, despite a small sample size, no complications were observed in a 30-day postoperative follow-up period of same-day discharge patients. Shaker et al 33 reported findings on immediate implant-based reconstruction, which found comparable rates to national standards in terms of postoperative infection, implant loss, and readmission rates, with no significant difference in overall complications. A series of studies by Dumestre et al 34 in 2017 reported similar data on implant-based reconstruction with same-day discharge compared with overnight admission, and focused on postoperative complications within a 30-day period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described outpatient surgical management of immediate implant-based reconstruction; however, each study has significant limitations that can be attributed to one of the following: poor group matching, small sample size, short-term follow-up, lack of controls, strict exclusion criteria (ie, DM, cardiovascular disease, high BMI, smokers, radiation therapy history), limited complication profile, unclear observation and outpatient definitions, or different pain management strategies or surgery settings between groups. 22,[25][26][27][28][29][30][31][32][33][34][35][36] Our study avoids many of these limitations and therefore provides a truer comparison of outpatient versus observation management.…”
Section: Resultsmentioning
confidence: 99%
“…Although several cohort studies and case series describe patients safely undergoing same-day immediate implantbased breast reconstruction, these studies have significant limitations. 22,[25][26][27][28][29][30][31][32][33][34][35][36] A true comparison between outpatient and inpatient management has not been performed. Therefore, we sought to compare the safety, complications, and cost differences between consecutive patients discharged on the same day of surgery compared with those admitted overnight for observation following immediate prosthetic breast reconstruction.…”
mentioning
confidence: 99%
“…Breast reconstruction surgery, specifically immediate breast reconstruction (IBR), has gained prominence in many developed countries as a means to address this challenge. Shaker et al demonstrated close to 90% day-case success rate for mastectomy with IBR [4]. While reconstruction rates vary globally from 5% to 50%, anecdotal evidence suggests that less than 1% of Pakistani women opt for reconstruction [5].…”
Section: Accepted Manuscriptmentioning
confidence: 99%